The Potential of Temporary Migration Programmes in Future International Migration Policy. - Ruhs, M (Wiley, 2006)
This article explores the potential of temporary migration programmes (TMPs) for managing international labour migration in a way that is both practical and sensitive. Drawing upon the experiences of past and current TMPs, Ruhs discusses how TMPs can: help high-income countries meet their market needs; provide people from low-income countries with better access to labour markets in higher-income countries; maximize migration's developmental impact on countries of origin; and address high-income countries' concerns about the permanent settlement of migrants and the diversity of their societies. In conclusion, he identifies the core considerations and policies needed to formulate and effectively implement TMPs.